Development of Android-Based Swimming Learning Media Mobile Learning Applications in Basic Swimming Lectures at Universitas Nahdlatul Ulama Blitar - Peni Nohantiya; Vion Age Tricahyo; Fatra Nonggala Putra (Journal of Development Research, 2024)
Mobile learning is widely used because of its ease that can be accessed anytime and anywhere, especially by students who have mobile devices such as smartphones, phablets or tablets. This research aims to develop Android-Based Swimming Learning Media Mobile Learning Applications in Basic Swimming Lectures at Universitas Nahdlatul Ulama Blitar. The method used by researchers is Research and Development (Adapted from Dick and Carey). The data was validated by 2 experts: media experts and swimming learning experts. Furthermore, a small group trial of 6 students was carried out, while 34 students were the subjects of the Large-Scale Trial. The results obtained are: Product clarity criteria obtained a percentage of 94.49% is very valid, attractiveness criteria are 92.40% very valid, Understanding Criteria 95.96% are very valid, and usefulness criteria 89.58% are very valid. All criteria have met the feasibility of the product so that the development of android-based swimming learning media mobile learning applications in basic swimming lectures is declared very valid and feasible to be used as a medium to maximize the learning process